2013
DOI: 10.7860/jcdr/2013/5307.3057
|View full text |Cite
|
Sign up to set email alerts
|

Profile of The Chikungunya Infection: A Neglected Vector Borne Disease which is Prevalent In The Rajkot District

Abstract: Background: Chikungunya Virus has been responsible for significant human morbidity probably for several hundred years; yet in spite of its prevalence, the Chikungunya Virus epidemiology and the mechanisms of virulence and pathogenesis are still poorly understood and undetermined. Aims:This study was done to show that the Chikungunya infection has shown a change in its pattern of occurrence with respect to the clinical features, the gender and the age group which are predominant and the season of the outbreak. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 11 publications
1
2
0
1
Order By: Relevance
“…At the time of sample collection, the average age of CHIKVseropositive donors was 41 years, and the average age of seronegative donors was 38 years. This is consistent with demographics previously reported for gender and age groups affected 35 . On average, blood donations for both groups were obtained six years post-infection.…”
Section: Study Donor Cohortssupporting
confidence: 93%
“…At the time of sample collection, the average age of CHIKVseropositive donors was 41 years, and the average age of seronegative donors was 38 years. This is consistent with demographics previously reported for gender and age groups affected 35 . On average, blood donations for both groups were obtained six years post-infection.…”
Section: Study Donor Cohortssupporting
confidence: 93%
“…However, in other studies higher prevalence in females has been reported [1417]. The reasons underlying these divergent observations remain elusive and are presumably linked with different habitats, economic factors and lifestyles.…”
Section: Discussionmentioning
confidence: 95%
“…Human induced pluripotent stem cells (IMR-90 ( Yu et al, 2007 )) were initially cultured on mouse embryonic fibroblast (MEF) feeders in hPSC medium and then expanded using either MEF-conditioned hPSC medium supplemented with 8 ng/mL human basic fibroblast growth factor (bFGF) or Essential 8™ (E8) medium on plates coated with growth factor-reduced Matrigel™ (1:60, v / v , cat No. CB-40230C, Fisher Scientific) ( Bhagwati et al, 2013 ; Chen et al, 2011 ). hPSC medium was prepared using KnockOut DMEM medium supplemented with 20% ( v / v ) KnockOut serum replacement, 0.5 mM l -glutamine, 0.1 mM nonessential amino acids, 0.1 mM beta-mercaptoethanol, 1% ( v / v ) PenStrep (10,000 IU/mL penicillin, 10,000 µg/mL streptomycin solution), and 4 ng/mL bFGF.…”
Section: Methodsmentioning
confidence: 99%